1968
DOI: 10.1099/0022-1317-2-1-29
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophage-tail-like Particles Associated with Intra-species Killing of Proteus vulgaris

Abstract: SUMMARYOne hundred and eighteen different strains of Proteus vulgaris were investigated for bacteriocinogeny. These and an additional 44 strains of P.vulgaris were used as indicators. Sixty-seven of the strains had a nontransmissible killing effect on one or more of the indicator organisms and 3o of these 67 bacteriocins with different spectra of activity were further investigated. Individual bacteriocins killed from 5 to 87 of the P. vulgaris indicators and a number of 44 different P. mirabilis strains but ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0

Year Published

1969
1969
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 3 publications
2
22
0
Order By: Relevance
“…The longitudinal length of enterocoliticin particles (ca. 80 nm) was clearly smaller than described for other particles of Enterobacteriacea, i.e., the length of carotovericin of Erwinia carotovora Er was 184 nm (27), the length of xenorhabdicin of Xenorhabdus nematophilus was 170 nm (31), and the proteocins of Proteus vulgaris had a length of 128 nm (11). The ultrastructural details of the enterocoliticin particles, including the measurements of tail length and diameter, resembled those of bacteriophages of the T-even phages (1) or coliphage Mu (32).…”
Section: Discussionmentioning
confidence: 99%
“…The longitudinal length of enterocoliticin particles (ca. 80 nm) was clearly smaller than described for other particles of Enterobacteriacea, i.e., the length of carotovericin of Erwinia carotovora Er was 184 nm (27), the length of xenorhabdicin of Xenorhabdus nematophilus was 170 nm (31), and the proteocins of Proteus vulgaris had a length of 128 nm (11). The ultrastructural details of the enterocoliticin particles, including the measurements of tail length and diameter, resembled those of bacteriophages of the T-even phages (1) or coliphage Mu (32).…”
Section: Discussionmentioning
confidence: 99%
“…Other workers (Taubeneck, 1963;Coetzee, de Klerk and Coetzee, 1968;Al-Jumaili, 1976) have found bacteriocin activity from Proteus strains to be associated with phage tail-like structures similar in morphology and dimensions to those of proticine 3. Although tail-like fibres, base plates and pins were not found with P. vulgaris bacteriocins (Coetzee et al, 1968) they appear to be present in proticine 3 and have been found in other bacteriocins from P. mirabilis (Al-Jumaili, 1976). These structures are important for attachment to specific receptor sites on the cell surface before contraction of the "nail" form to the "rocket" form.…”
Section: Discussionmentioning
confidence: 99%
“…These structures are important for attachment to specific receptor sites on the cell surface before contraction of the "nail" form to the "rocket" form. Biological activity is thought to be associated only with the "nail" form of the particulate bacteriocins (Coetzee et al, 1968;Higerd, Baechler and Berk, 1969). Higerd et al (1969) reported that the conversion reaction of "nails" to "rockets" is reversible for pyocines although the conversion of a "rocket" back to a "nail" did not restore biological activity; it appeared that the lethal activity was lost in the initial change of a "nail" into a "rocket" form.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, electron microscopic studies have revealed that the structure of some bacteriocins resembles a phage-like object or phage component such as the tail assembly. (Endo et al 1965;Meningmann, 1965;Sandoval, Reilly & Tandler, 1965; Ishii, Nishi & Egami, 1965; Bradley & Dewar, 1966; Higerd, Baechler & Berk, 1967;Bradley, 1967;Lang, McDonald & Gardner, 1968;Coetzee et al 1968).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, electron microscopic studies have revealed that the structure of some bacteriocins resembles a phage-like object or phage component such as the tail assembly. (Endo et al 1965;Meningmann, 1965;Sandoval, Reilly & Tandler, 1965; Ishii, Nishi & Egami, 1965; Bradley & Dewar, 1966; Higerd, Baechler & Berk, 1967;Bradley, 1967;Lang, McDonald & Gardner, 1968;Coetzee et al 1968).Ishii et aL (1965) showed that a trypsin-resistant pyocin, a bacteriocin of Pseudomonas aeruginosa closely resembles T-even phage tails with a contracti/e sheath. Takeya et al (1966) isolated a small pyocin with a different morphology and designated it pyocin 28.…”
mentioning
confidence: 99%